2018
DOI: 10.1021/acs.analchem.7b04684
|View full text |Cite
|
Sign up to set email alerts
|

Four Hapten Spacer Sites Modulating Class Specificity: Nondirectional Multianalyte Immunoassay for 31 β-Agonists and Analogues

Abstract: Immunoassay methods are important for monitoring β-agonists illegally used for reducing animal fat deposition in livestock. However, there is no simultaneous screening surveillance immunoassay for detecting various β-agonist chemicals that are possibly present in food. In this study, through the use of an R-(-)-salbutamol derivative as the immunizing hapten, an antibody recognizing 31 β-agonists and analogues was generated for the first time. Three-dimensional quantitative structure-activity relationship (3D Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 35 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…For example, Mercader et al produced a high-affinity anti-pyraclostrobin antibody by synthesizing a series of anti-pyraclostrobin haptens with the same aliphatic linkers located at different sites, and found that the lower titers and affinities of one set of antibodies were most likely due to the conformational effects of the linker on the immunizing bioconjugate [19]. Wang et al found that four linker sites on R-(−)-salbutamol modulating the class specificity of the resultant antibodies against 31 β-Agonists [20]. However, for smaller molecules like HA, acrylamide, ethyl carbamate and 3-amino-2-oxazolidinone (AOZ) with simpler structure and limited site for tethering the linker, shifting the linker site exerted negligible effect on the quality of the resultant antibodies, since almost all of the resulting antibodies against conventionally designed haptens exhibited low titer and negligible affinity for target molecules (as summarized in Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Mercader et al produced a high-affinity anti-pyraclostrobin antibody by synthesizing a series of anti-pyraclostrobin haptens with the same aliphatic linkers located at different sites, and found that the lower titers and affinities of one set of antibodies were most likely due to the conformational effects of the linker on the immunizing bioconjugate [19]. Wang et al found that four linker sites on R-(−)-salbutamol modulating the class specificity of the resultant antibodies against 31 β-Agonists [20]. However, for smaller molecules like HA, acrylamide, ethyl carbamate and 3-amino-2-oxazolidinone (AOZ) with simpler structure and limited site for tethering the linker, shifting the linker site exerted negligible effect on the quality of the resultant antibodies, since almost all of the resulting antibodies against conventionally designed haptens exhibited low titer and negligible affinity for target molecules (as summarized in Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…The CoMFA and CoMSIA models were used to analyze the interaction between the antibody and AOH‐like compounds, that is, simulations of the binding process were performed in the electrostatic field, steric field, hydrophobic field, and in the field of the hydrogen bond donor and acceptor . In the CoMFA model, the values of q 2 and r 2 were 0.785 and 0.911, respectively, while the values of q 2 and r 2 were 0.782 and 0.998, respectively, in the CoMSIA model.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of the antibody crystal structure, 3D‐QSAR can reasonably explain the difference in the CR and effectively predict and elucidate the mechanisms for antibody recognition . Wang et al prepared an antibody that can recognize 31 β‐agonists and analogues, thoroughly analyzing the key factors affecting hapten design and antibody recognition through 3D‐QSAR . Chen et al explained the effect of quinolone hapten conformation on the specificity of antibody through 3D‐QSAR, proposing a hapten design strategy for developing the class specificity immunoassay .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential binding sites and modes of antibody-analyte recognition can be predicted by molecular docking and computational chemistry techniques [22]. With the help of these novel computer-assisted strategies, the most appropriate hapten chemical structure can be selected without a large number of experiments [23]. Xu et al [24] used 2D and 3D quantitative structure-activity relationships (QSARs) to increase the sensitivity and investigate antibody recognition.…”
Section: Preparation and Application Of Generic Antibodiesmentioning
confidence: 99%